A Companion to ethics - Singer, Peter, ed. (Oxford : Blackwell, 1993)
In this volume, some of today's most distinguished philosophers survey the whole field of ethics, from its origins, through the great ethical traditions, to theories of how we ought to live, arguments about specific ethical issues, and the nature of ethics itself. The book can be read straight through from beginning to end; yet the inclusion of a multi-layered index, coupled with a descriptive outline of contents and bibliographies of relevant literature, means that the volume also serves as a work of reference, both for those coming afresh to the study of ethics and for readers already familiar.
PART I: THE ROOTS; 1 The origin of ethics; i The search for justification; ii The lure of egoism and the social contract; iii Moral and factual arguments; iv Dualistic fantasies; v The advantages of ethnology; vi Two objections; vii Sociability, conflict and the origins of morality; viii The problem of partiality; ix Is morality reversible?; x Conclusion; 2 Ethics in small-scale societies; 3 Ancient ethics; i Ethics in ancient Mesopotamia; ii Ethics in ancient Egypt. Iii Ethics in the Hebrew ScripturesPART II: THE GREAT ETHICAL TRADITIONS; 4 Indian ethics; i Brahmanical-Hindu ethics; ii Jaina ethics; iii Gandhian ethics; iv Concluding remarks; 5 Buddhist ethics; i Introduction; ii Ethical concerns in the Buddhist tradition; iii The moral philosophy of Buddhism; iv A Buddhist perspective on the place of knowledge and truth in ethics; v Buddhism as an ethics of virtues and vices; vi Buddhist social ethics; vii Buddhist perspectives on practical ethics; viii Contributions to ethics in the later Buddhist traditions; 6 Classical Chinese ethics. I The positive Dao period: Confucius and Moziii The anti-language period: Yangzhu, Mencius and Laozi; iii The schools of names: formal meta-ethics; iv Zhuangzi: Daoist relativism; v Xunzi: pragmatic Confucianism; vi The Dark Ages: the end of the Hundred Schools; vii The continuing impact of classical thought; 7 Jewish ethics; 8 Christian ethics; i A survey of Christian faith and ethics; ii Jesus; iii St Paul; iv Criticisms of Christian ethics; 9 Islamic ethics; i Introduction; ii Beginnings and development: foundational values; iii The theological and traditionalist approaches. Iv Philosophical approaches Ethics in the Shi'a tradition; vi Sufi perspectives; vii Muslim ethics in the contemporary world; PART III: WESTERN PHILOSOPHICAL ETHICS: A SHORT HISTORY; 10 Ethics in ancient Greece; i Historical outline; ii Themes and issues in Greek ethics; 11 Medieval and Renaissance ethics; i Introduction; ii From the Church Fathers to the scholastics; iii The golden age of scholasticism
Includes bibliographical references and index
Keywords: Ethics; Social ethics